ERK2 and Akt are negative regulators of insulin and Tumor Necrosis Factor-α stimulated VCAM-1 expression in rat aorta endothelial cells. Issue 1 (December 2016) - Pott, Gregory; Tsurudome, Mark; Bamfo, Nadia; Goalstone, Marc
Abstract Background Diabetes is quickly becoming the most widespread disorder in the Western world. Among the most prevalent effects of diabetes is atherosclerosis, which in turn is driven in part by inflammation. Both insulin and Tumor Necrosis Factor-alpha (TNFα) increase the presence of Vascular Cellular Adhesion Molecule-1 (VCAM-1) expression. The aim of this study is to determine the effects of downregulating Extracellular signal-Regulated Kinase-2 (ERK2) and Akt on insulin and TNFa-stimulated VCAM-1 expression. Methods Here we begin to define the relationships between ERK2 and Akt regulation of insulin and TNFα-stimulated VCAM-1 expression in Rat Arterial Endothelial Cells (RAEC) by transfecting RAEC with ERK2 and Akt RNA interference (RNAi) and then treating these cells with insulin (10 nM) or TNFα (10 ng/mL) alone or in combination. Results Western blot analyses, flow cytometry and confocal microscopy were used to determine changes in VCAM-1 expression within the above-stated parameters. Cells transfected with ERK2 or Akt RNAi plasmids increased insulin and TNFα-stimulated VCAM-1 total protein expression significantly (P  < 0.05) greater than that seen in mock transfected cells and expressed cell surface VCAM-1 greater than that seen in mock transfected cells as indicated by flow cytometry and confocal microscopy. Nevertheless, the decrease of both kinases did not increase insulin or TNFα-stimulated VCAM-1 expression above that seen when one or the other RNAi was present. Conclusions Taken together, our results demonstrate that ERK2 and Aktmay be negative regulators of insulin and TNF-α stimulated VCAM-1 and that their loss or down regulation might upregulate VCAM-1 expression and contribute to vascular disease.